2011
DOI: 10.2139/ssrn.1939767
|View full text |Cite
|
Sign up to set email alerts
|

How Do Banks’ Funding Costs Affect Interest Margins?

Abstract: Abstract:We use a dynamic factor model and a detailed panel data set with quarterly accounts data on all Norwegian banks to study the effects of banks' funding costs on their retail rates. Banks' funds are categorized into two groups: customer deposits and long-term wholesale funding (market funding from private and institutional investors including other banks). The cost of market funding is represented in the model by the three-month Norwegian Inter Bank Offered Rate (NIBOR) and the spread of unsecured senio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The study found clear evidence showing pass through from the NIBOR to the loan rates. Similarly, Raknerud et al (2011) examined the impact of bank funding costs on interest margin on Norwegian banks. The study used dynamic factor model and panel data set with quarterly accounts data.…”
Section: Empirical Studiesmentioning
confidence: 99%
“…The study found clear evidence showing pass through from the NIBOR to the loan rates. Similarly, Raknerud et al (2011) examined the impact of bank funding costs on interest margin on Norwegian banks. The study used dynamic factor model and panel data set with quarterly accounts data.…”
Section: Empirical Studiesmentioning
confidence: 99%
“…He also finds that the rates of liquid and well-capitalised banks react less to changes in official rates, but that bank size is not relevant. Cecchin (2011) and Raknerud, Vatne, and Rakkestad (2011) find evidence that pass-through is sluggish and incomplete for Swiss and Norwegian banks respectively. Gambacorta and Mistrulli (2011) analyse interest rate pricing in Italy following the collapse of Lehman Brothers.…”
Section: Theory and Literaturementioning
confidence: 99%
“…The hypothesis that r t is not a unit root process was considered in Raknerud et al (2011), using both daily data and quarterly data, applying the test proposed by Choi (1994). The null hypothesis of stationarity against the alternative that r t is a unit root process was not rejected.…”
Section: Examining the Stationarity Of The Dependent And Exogenous Variablesmentioning
confidence: 99%
“…The period analyzed in this paper -2002Q1 to 2011Q3 -includes a period of financial distress and is also characterized by increased competition and productivity growth due to rapid increase in Internet-based payment services. One effect of the latter is that the interest margin between loan rates and deposit rates has decreased steadily over the period (or at least until the financial crisis), as documented in Raknerud et al (2011).…”
Section: Introductionmentioning
confidence: 99%